Challenges, Dilemmas and Achievements of Internal Evaluation in University Degree - Judit Fullana Noell; Maria Pallisera Díaz; Anna Planas Lladó; Montse Tesouro Cid (Universidad Autónoma de Madrid, 2016)
The evaluation of the quality of the higher education has been subject of analysis and debate from more than a decade in Spain. In the new stage of the higher education, marked by the process of European convergence, reflection on the concept and processes of university quality assurance has increased. One of the visible consequences of the development of the European Space of Higher Education has been that the National Agency of Evaluation of the Quality (ANECA), requires including the design of the quality assurance system in the formal planning documents of the degrees. In this article we talk about how we can incorporate the internal systems of quality evaluation as a part of the ordinary running of degrees so that they become an indispensable element to develop the culture of quality in the university context. We explain the current context of the internal evaluation of the quality in the Spanish universities and, from our experience in the implementation of the system of internal evaluation for the Degree of Social Education at the University of Girona, we reflect on the main challenges we need to face to develop these evaluation systems of the quality and its integration in the regular running of the degrees.